The impact of smoking on patient outcomes in severe sepsis and septic shock - Alroumi, Fahad (J Intensive Care, 2018)
BACKGROUND: To assess, in the setting of severe sepsis and septic shock, whether current smokers have worse outcomes compared to non-smokers. METHODS: This is a retrospective analysis of immunocompetent adult patients with severe sepsis and septic shock at a tertiary medical center. The primary outcome was the effect of active smoking on hospital mortality. Chi-square test and logistic regression were used to assess categorical outcomes. Wilcoxon rank-sum was utilized to test the differences in continuous outcomes among the varied smoking histories. Multivariable logistic regression was used to evaluate the association of smoking and mortality, need for vasopressors, mechanical ventilation, and ICU admission. RESULTS: Of the 1437 charts reviewed, 562 patients were included. Current smokers accounted for 19% (107/562) of patients, while 81% (455/562) were non-smokers. The median hospital length of stay in survivors was significantly longer in current smokers versus non-smokers (8 vs 7 days, p = 0.03). There was a trend towards a higher mortality among current smokers, but this failed to meet statistical significance (OR 1.81, 95% CI 0.92–3.54, p = 0.08). On multivariable analysis, current smoking was associated with the need for mechanical ventilation (OR 2.38, 95% CI 1.06–5.34, p = 0.04), but that association was not observed with the need for vasopressors (OR 2.10, 95% CI 1.01–4.36, p = 0.58) nor ICU admission (OR 0.93, 95% CI 0.41–2.13, p = 0.86). CONCLUSIONS: In patients with severe sepsis or septic shock, current smoking was associated with a longer hospital stay, the need for mechanical ventilation, and trended towards a higher mortality. Larger multicenter prospective case-control studies are needed to confirm these findings.